1985
DOI: 10.1159/000145954
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Somatostatin 14 on Mouse Stomach, Antrum, Intestine and Exocrine Pancreas

Abstract: Mice were injected 3 times a day for 12 days with 8 µg/kg of somatostatin 14 which caused ahypoplasia of parietal and goblet cells, a hypotrophy and hypofunctionality of pancreatic acinar cells with a decrease in lipase and chymotrypsin activities, a decrease in the secretory function of the Brunner gland and in the number of dark granules of G cells. Neither villous and microvillous areas nor brush border hydrolase activities were affected. The number of peptic cells and Paneth cells increase as the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Somatostatin on the other hand is thought to inhibit growth or to have antitrophic effects on the pancreas [Morisset et al. 1982: Senegas-Balas et al. 1985, Somatostatin-immunoreactive cells within the pan creas show a relative decrease in number during the period of rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin on the other hand is thought to inhibit growth or to have antitrophic effects on the pancreas [Morisset et al. 1982: Senegas-Balas et al. 1985, Somatostatin-immunoreactive cells within the pan creas show a relative decrease in number during the period of rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin-14 has been shown to inhibit exocrine pancreatic secretion [29,30] and the release of gastrointestinal hormones like CCK [31]. It is suggested to be an antigrowth factor for the pancreas [59][60][61][62]. Due to the short halflife of this peptide continuous administra tion or multiple subcutaneous injections of high doses are required to establish long term effects on pancreatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the short halflife of this peptide continuous administra tion or multiple subcutaneous injections of high doses are required to establish long term effects on pancreatic growth. Mice in jected with 8 pg/kg somatostatin-14, 3 times daily, showed hypotrophy of pancreatic aci nar cells with a decreased number of zy mogen granules after 12 days [62], Chronic administration of extremely high doses of somatostatin-14, 100-600 pg/kg, in rats re sulted in discrete reductions of pancreatic protein and DNA levels [59].…”
Section: Discussionmentioning
confidence: 99%
“…Lehy et al 39 and Senegas-Balas et al 40 showed that somatostatin decreased the labeling index of fundic, antral, duodenal, and jejunal cells. Cascinu et al 19 found that octreotide significantly reduced the S-phase fraction in patients with colorectal cancer measured by both [ 3 H]thymidine labeling index and flow cytometry.…”
Section: Discussionmentioning
confidence: 99%